Titanium oxide nanowire clots with two-phase composition as multi-effect sulfur reservoirs for lithium-sulfur batteries. (September 2021) - Cai, Yuqing; Yan, Zhongyuan; Shi, Shumin; Zhang, Lida; Zhang, Ting; Yang, Mingtong; Bai, Ling; Fu, Hui; Yang, Xu-Sheng; Li, Ziquan; Huang, Zhen-Dong
Abstract: Lithium-sulfur battery (LSB) is one of the most promising battery systems for green energy plants and electric vehicle power sources. A high-performance sulfur reservoir is one of the most critical components for LSBs to protect the soluble lithium polysulfides (LPSs) from shuttling to lithium anode. Herein, titanium oxide nanowire clots (TOCs) with a two-phase composition and high effective absorption surface area (270.1 m 2 g −1 ) are designed as promising reservoirs to accommodate sulfur and LPSs. The synergistic effects generated from the unique structure of TOCs make the obtained S/TOCs cathode materials exhibit high specific capacity, high coulombic efficiency, and excellent cyclic stability at 1C and 2C rates. The corresponding capacity fading rates per cycle are around 0.14% and 0.11 % for the LSBs being (dis)charged 1C and 2C, respectively. Graphical abstract: Titanium oxide nanowire clots with a two phase composition and high effective absorption surface area are developed as the promising reservoirs for the accommodation of sulfur and lithium polysulfides. Lithium-sulfur batteries coupled with S/titanium oxide nanowire clots composite cathode deliver an excellent cyclic stability and rate capability Image, graphical abstract .